Theoretical and philosophical framework for individualised care - Papastavrou, Evridiki; Igoumenidis, Michael; Lemonidou, Chryssoula (My University, 2018)
Individuality plays a central role in human existence. Its realisation varies greatly in different historical times and places. In modern societies it can often be under threat, under the influence of mass media and mass production, but its importance is recognised, and there have been constant efforts to enhance it. In health services, holistic care for individual patients has become a milestone goal. Individualised care can improve patient outcomes in an ethical and respectful way. Despite the difficulties posed by modern health-care delivery, an increasing number of studies ascertain the importance of individualised care. Based on the existing evidence, various health-care organisations recognise the need to enhance individualised care and implement various initiatives to do so. However, various economic constraints do not allow for wide implementation of individualised health interventions. Technological progress provides more opportunities than ever for individualised care, but limited health resources set a series of obstacles for its delivery. Further research in this field shall help towards embodying the best affordable individualised care in modern health delivery.
Keywords: Humoral medicine; Individualised care; Individuality concept; Patient advocacy; Personalised medicine